Evaluation of the environmental risk of a natural physical type and its relationship with urban planning. Case: Comas district - Valdivia Fernández, Helga (2004)
The lack of planning of the territory has defined the existence of urban scenarios that are not very functional and lacking in environmental physical security, defending populations settled in areas of very high and high natural environmental danger due to the natural conditions and physical characteristics of the place, situation that puts the lives of its inhabitants, the infrastructure of their homes, urban facilities and basic services at risk, making awareness of the probability of the occurrence of urban disasters extremely important, which is why this project was prepared research. Developing this experience in the second most populated district in our country: «The Comas district». Numerous populations are identified that are vulnerable to various natural type environmental hazards that have occurred and are likely to occur in the study area. Among them: mud flow, rockfall, landslides, groundwater outcrop, flooding due to the overflow of the Chillón river, river bank erosion, activation of the existing geological fault system in the study area, among others. The existing urban disorder has given rise to the development of environmental physical problems such as: urban occupation in areas of very high and high natural physical danger, urban occupation in areas severely damaged by structural tectonics, urban occupation in areas of moderate physical environmental danger (due to flooding due to the outcrop of groundwater and overflows of the Chillón river), high levels of air pollution and / or deficit of green areas, deficit and restriction of basic services, loss of agricultural areas due to urban occupation, deterioration of archaeological zones, deterioration and loss of natural ecosystems. For all this, that the evaluation of environmental risk of a natural physical type and others of great importance in the study area, allows designing strategies and actions for their prevention and mitigation, through the strengthening of natural disaster management. and the urban environmental management of the district.